L'étudiant en IUT : du singulier au pluriel - Florian Olivier
At the occasion of the fiftieth birthday of the IUT's creation, this article aims at providing an overview of their students profile from the perspective of an explorative research. We will show that if IUT's students can be seen as average students, which is consistent with the average position of the IUT in the structured field that is higher education, this general picture masks however a more complex reality with on the one hand an opposition between commercial and industrial formations which repeats the symbolic prima of scientific majors and its consequences in terms of gender or social differences; on the other hand, with the paradox of students socially closer to those from the faculties, but culturally and morally tied with the ones from technician sections, often coming from the working-class.